Influential factors on the therapeutic response in the conditioning treatment of enuresis with an original therapeutic machine - Ikuhara, Y (Hinyokika kiyo. Acta urologica Japonica, 1993)
The conditioning treatment of enuresis with our original therapeutic machine, that is to awake the patient before enuresis may occur, has been performed since 1987. Influential factors on the therapeutic response were investigated. Twenty two patients with enuresis Type I were admitted and were treated for 5 nights with the therapeutic machine. Seven patients were cured (the cured group) and a certain effectiveness (decrease of the frequency of enuresis of more than 50%) was observed in 8 patients (the effective group). No effectiveness was obtained in 7 patients (the no change group). The average age of the cured group was higher than that of the no change group, and the difference was significant. No significant differences were found among the three groups in sex, the frequency of enuresis or the past experience of awakening before enuresis. Significant differences among the three groups were found in the average awakening score (how easily the patient awoke when a nurse called the patient after the machine alarmed) and the change of awakening score during treatment. The average awakening score of the cured group was the highest and that of the no change group was the lowest. The change of awakening score during treatment of the no change group was significantly lower than that of the cured group or that of the effective group. The desire to cure, scored 0-2 points at the time of discharge, was significantly stronger in the cured group than in the no change group. No significant differences were noticed among the three groups in the sleeping condition and the remembrance of awakening at the next morning